2007
DOI: 10.1111/j.1365-2591.2007.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of new resin‐, calcium hydroxide‐ and silicone‐based root canal sealers on fibroblasts derived from human gingiva and L929 cell lines

Abstract: Toxicity varied but RC Sealer and GuttaFlow were the least toxic new sealers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
124
2
24

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(177 citation statements)
references
References 53 publications
(108 reference statements)
27
124
2
24
Order By: Relevance
“…As reported by some authors (15), changes in culture and subculture media have varied intervals according to the used cell line. Therefore, the line should be properly considered when selecting a subculturing protocol, and choose the protocol that causes the least damage to the cells, as advocated by other authors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As reported by some authors (15), changes in culture and subculture media have varied intervals according to the used cell line. Therefore, the line should be properly considered when selecting a subculturing protocol, and choose the protocol that causes the least damage to the cells, as advocated by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…For surface disinfection, test specimens were exposed to ultraviolet light (14,25), for approximately 30 h. However, some authors (14) used a 2-h period whereas others (25) used a 24-h period. This type of incubation used in the present study to assess the effect of the sealers on ECV-304 cells has been used elsewhere (13,15,(23)(24)(25). A previous study (13) also used ECV-304 cells that were incubated at 37ºC in 5% CO 2 and 100% humidity for 7 days and cultured in an F12 medium supplemented with 10% fetal bovine serum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…111 However, it has also been demonstrated that although Epiphany was cytotoxic it did not effect the viability of human leucocytes. 112 The reported cytotoxicity may be due to the leakage of uncured monomer from the oxygen inhibition layer, 100,101,113,114 or due to the degradation of the sealer in an aqueous environment. [115][116][117] The Bis-GMA and UDMA contained within the Epiphany bonding agent are another potential source of cytotoxicity.…”
Section: Biocompatibilitymentioning
confidence: 99%